The effects of temporal continuities of grasslands on the diversity and species composition of plants. Issue 1 (1st September 2020) - Inoue, Taiki; Yaida, Yuki A.; Uehara, Yuki; Katsuhara, Koki R.; Kawai, Jun; Takashima, Keiko; Ushimaru, Atushi; Kenta, Tanaka
Abstract: Seminatural grasslands are ecosystems rich in biodiversity. However, their decline has been reported worldwide, and identification of grasslands with high conservation priority is urgently required. Recently, an increasing number of studies have reported that past vegetation history affects current biological communities. To evaluate whether the temporal continuity of grasslands promotes biodiversity, and thus can be an indicator of conservation priority, we studied vascular plant communities in old (160–1000s years) and new (52–70 years after deforestation) grasslands, as well as in forests, of Sugadaira Highland in central Japan. The number of plant species was highest in old grasslands, followed by new grasslands and forests. This pattern was much clearer in the number of grassland‐dependent native and grassland‐dependent endangered species, indicating the role of old grasslands as refugia for those species. The species composition differed between old and new grasslands. New grasslands had species compositions in between those of old grasslands and forests, suggesting that the plant community in new grasslands retains the influence of past forestation for more than 52 years after deforestation. Eleven indicator species were detected in old grasslands, but none in new grasslands, suggesting the uniqueness of the plant community in old grasslands. We conclude that the temporal continuity of grasslands increases plant diversity and can be an indicator of grasslands with high conservation priority. Abstract : We compared plant diversity and species composition in old and new grasslands and forests. The old grasslands had high plant diversity and unique plant communities. Thus, it is proposed that old grasslands have high conservation priority and are where conservation effort should be concentrated. Horizontal and vertical axes represent the first and the second axes extracted by nonmetric multidimensional scaling, respectively.